Arbitrase : ditinjau dari : Reglemen acara perdata (RV), peraturan prosedur BANI, Intenational Centre for the settlement of invesment disputes (ICSID), UNCITRAL arbitration rules, Convention on the recognition and enforcement of foreing arbitral award, PERMA No. 1 tahun 1990 - Harahap, M. Yahya (Sinar Grafika, 2006)
xi, 376 p.; 23 cm